Peningkatan Status Gizi Balita Dengan Gizi Buruk Melalui Pemberian Formula 100 - Murwati Murwati; Tuti Devianti (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: Provision Of Formula 100, The Toddler Nutritional Status. Malnutrition is still a serious problem in Indonesia which frequently occur in groups of children aged under five years. The incidence of malnutrition if not addressed will cause a negative effect on children, among other death and chronic infections. Number of children under five in the region Puskesmas Sukoharjo in late December 2013 as many as 4109 children, identified under five suffering from severe malnutrition as many as 32 children. This study was to determine the effect of formula 100 to the nutritional status of children in the region Puskesmas Sukoharjo. Ekspriment quasi design with the design of one group pre test post test design. Populations of all infants with malnutrition in Puskesmas Sukoharjo Sukoharjo number 32 toddlers. Purposiv Sampling Techniques number 26 toddlers. Statistical test bivariate analysis with paired sample t-test with a confidence level of 95% or  = 5%. Results of the study, the average age of a toddler 30.77 a month and 76.9% of women. Nutritional status of children before giving formula 100 wholly severe malnutrition. After administration of 100 formula, infant malnutrition status as much as 69.2% 26.9% good nutritional status and poor nutritional status 1 child (3.8%). The test results paired sample t-test showed no effect of formula 100 to the nutritional status of children in the region Puskesmas Sukoharjo (p = 0.001). In conclusion there is the influence of formula 100 to the nutritional status of children in the region Puskesmas Sukoharjo.